High-thixotropy cement-based material for wet pressing

By using highly thixotropic cement-based materials, the problem of insufficient fluidity of wet-pressed cement-based materials is solved, cement products with complex shapes can be pressed, and material strength and production efficiency are improved.

CN119349952APending Publication Date: 2025-01-24BEIJING MUNICIPAL ENG RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411468199.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing wet pressed cement-based materials are insufficient in pressing complex-shaped cement products and cannot quickly fill the special-shaped mold, resulting in material shortage and other problems.

Method used

It adopts a highly thixotropic cement-based material made of cement, aggregate, fly ash, silica fume and admixtures. The material becomes plastic after mixing with water, has excellent thixotropic properties and can flow rapidly under the action of external force. and filled with mold.

Benefits of technology

The complex shape suppression of cement products is achieved, the density of the material is increased by 3-5%, the intensity is increased by about 40%, and it can be immediately removed, which can improve production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349952A_ABST
    Figure CN119349952A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to a high-thixotropy cement-based material for wet pressing. The high-thixotropy cement-based material for wet pressing is prepared from the following raw materials: cement, aggregate, fly ash, silica fume and an additive. The cement-based material for wet pressing has unique performance, has no fluidity after being added with water and stirred, is in a plastic state, can be fed into the lower part of a press mold in a block shape, has excellent thixotropic performance, has excellent fluidity under the action of external force, and can quickly fill the mold and form any required shape. Meanwhile, in the pressing process, part of free water in the material can be extruded and discharged, so that a compact cement product capable of being directly demolded is formed, and the strength of the cement-based material cured to final strength is higher than that of a cement-based material prepared by a common pouring process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to a high-thixotropic cement-based material for wet pressing. Background Art

[0002] The pressing process of cement products is currently mainly divided into two methods: dry vibration pressing and wet pressing. Dry vibration pressing is a process that uses stone powder, fly ash, slag, slag, gravel, sand, water, etc. as raw materials, stirs them into dry hard concrete, and then squeezes them into shape through vibration. At present, more than 80% of the pressed cement products on the market are formed by this method, which is characterized by high efficiency, low cost and low quality. Wet pressing is to first add water to the cement-based material and stir it to a plastic state, then feed it into a pressing mold with a water filtration function, and use a high-pressure press to press the plastic cement-based material into a dry hard type, and squeeze out part of the water. This process has the characteristics of high material strength, delicate texture and diverse shapes compared to dry molding. It is currently mainly used in the production of products such as raised floors, cement tiles, and cement-based curbstones.

[0003] With the development of the market, the requirements for the shape of cement products are getting higher and higher. However, the dry vibration pressing molding and wet pressing methods can only produce plates with simple shapes. For cement products with complex shapes, only the inefficient casting method can be used.

[0004] According to research, the main technical barrier restricting the pressing of complex cement products is the lack of fluidity of pressed cement-based materials, which makes it impossible to fill the cavity of special-shaped molds. A large number of experiments have shown that materials formed by dry vibration pressing have basically no fluidity, and only wet pressed materials have a certain fluidity under pressure, which has the potential to press complex cement products. However, when experiments were conducted with the proportion of conventional wet pressed cement-based materials, their fluidity still could not meet the needs of complex cement products, especially when the cement-based materials could not quickly fill the mold during pressing, resulting in problems such as material shortage.

[0005] Thixotropy of cement slurry refers to the property that cement slurry becomes thinner after being stressed and thicker after being still. That is, under the action of a certain shear rate, the apparent viscosity of cement slurry gradually decreases with the extension of the action time and tends to a certain value, or when the shear action stops, the apparent viscosity of cement slurry increases again, but does not necessarily return to its original shape. Summary of the invention

[0006] Based on the above technical background, the main purpose of the present invention is to provide a high thixotropic cement-based material for wet pressing. The cement-based material for wet pressing has its unique properties. After adding water and stirring, it has no fluidity and is in a plastic state. It can be fed into the lower part of the press mold in a block, but it has excellent thixotropic properties and has excellent fluidity under the action of external force. It can quickly fill the mold and form any desired shape. At the same time, during the pressing process, part of the free water in the material will be squeezed out to form a dense cement product that can be directly demolded. After curing to the final strength, the strength is higher than that of cement-based materials with ordinary casting processes. The present invention uses a concrete rheometer to test it, and tests its static yield stress, dynamic yield stress and plastic viscosity to characterize the thixotropy, so as to overcome the deficiency that the existing cement-based material detection technology cannot detect its thixotropy.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] The present invention provides a high thixotropic cement-based material for wet pressing, characterized in that the high thixotropic cement-based material for wet pressing is made from raw materials including cement, aggregate, fly ash and silica fume;

[0009] The mass ratio of the cement, aggregate, fly ash, silica fume and admixture is (0.6-0.9):(1-3):(0.1-0.3):(0.01-0.1).

[0010] Preferably, the mass ratio of the cement, aggregate, fly ash, silica fume and admixture is 0.75:2:0.20:0.05.

[0011] Preferably, the aggregate comprises sand and gravel, and the particle diameter of the aggregate is between 0.16 and 5 mm.

[0012] More preferably, the mass ratio of the sand to gravel is (2-4):1.

[0013] More preferably, the mass ratio of the sand to the gravel is 3:1.

[0014] Preferably, the raw materials further include water, and the ratio of the added amount of water to cement is (0.3-0.5):(0.6-0.9).

[0015] Preferably, the raw material further includes an admixture, and the ratio of the amount of the admixture to the amount of cement added is (0.005-0.01): (0.6-0.9).

[0016] More preferably, the admixture includes naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate, and sodium gluconate.

[0017] More preferably, the mass ratio of the naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate and sodium gluconate is 0.8-0.9: 0.002-0.006: 0.001-0.004: 0.03-0.06.

[0018] The beneficial effects of the present invention are:

[0019] (1) The high thixotropic cement-based material for wet pressing of the present invention is made of raw materials including cement, aggregate, fly ash, silica fume and admixtures, and has unique properties. After adding water and stirring, it has no fluidity and is in a plastic state, but has excellent thixotropic properties. It has good fluidity under the action of external force and can quickly fill the mold and form any desired shape.

[0020] (2) The cement-based material for wet pressing described in the present invention is suitable for high-pressure compaction molding due to its unique properties. It can be pressed into block-shaped cement prefabricated component materials with complex internal structures (ordinary cement-based materials can only be pressed into plate-shaped materials). The high-pressure compaction molding method adopted does not evenly distribute the energy to the entire volume of the concrete, but concentrates it on the upper and lower surfaces of the module. The stress is more concentrated, making the concrete prone to shear displacement and particles can easily move. In this way, under the action of external pressure, the mixture undergoes exhaust and volume compression processes, which gradually spread to the whole, and finally achieves a better compaction molding effect. The density can be increased by 3-5%, and the concrete strength can be increased by about 40%.

[0021] This molding method can be demoulded immediately, improving the turnover rate and production efficiency of the equipment.

[0022] This forming method solves the problems of bubbles and blisters generated on the surface of concrete structures during the concrete pouring operation, as well as surface defects and problems such as surface leakage, hanging curtains, misalignment, and roughness. It treats these common and frequent "common and frequently occurring diseases", improves the physical quality image of concrete projects, and strengthens the brand image of the enterprise.

[0023] (3) The cement prefabricated component module made of the high thixotropic cement-based material by wet pressing of the present invention has small corner thickness deviation, high precision, stable structure, high bearing capacity, can be laid overhead, and realizes the separation of water and electricity pipelines. It is suitable for new products of different shapes and sizes, with high degree of standardization and commercialization, adapting to diversified decoration styles and matching the needs of owners.

[0024] The molding method of the present invention can improve the standardization of prefabricated components, make the specifications of prefabricated components more comprehensive, the forms more diverse, and easily form industrial clusters, promote technological innovation of production methods, reduce on-site wet operations, promote environmental protection and ecological concepts, achieve comprehensive factory prefabrication, and improve social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram showing the microstructure of concrete formed by wet pressing of a highly thixotropic cement-based material according to the present invention;

[0026] Figure 2 A schematic diagram showing a concentric cylinder structure;

[0027] Figure 3 A schematic diagram of the test procedure is shown;

[0028] Figure 4 The stress growth curves of various embodiments and comparative examples are shown;

[0029] Figure 5 The fitting curve of Example 1 in Experimental Example 1 is shown;

[0030] Figure 6 The fitting curve of Example 2 in Experimental Example 1 is shown;

[0031] Figure 7 The fitting curve of Example 3 in Experimental Example 1 is shown;

[0032] Figure 8 The fitting curve of Comparative Example 1-1 is shown;

[0033] Fig. 9 The fitting curve of Comparative Example 1-2 is shown;

[0034] Fig.10 The fitting curves of Comparative Examples 1-3 are shown;

[0035] Fig.11 The fitting curve of Comparative Example 2-1 is shown;

[0036] Fig.12 The fitting curve of Comparative Example 2-2 is shown; DETAILED DESCRIPTION

[0037] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.

[0038] The first aspect of the present invention is to provide a high thixotropic cement-based material for wet pressing, wherein the high thixotropic cement-based material for wet pressing is made from raw materials including cement, aggregate, fly ash and silica fume.

[0039] The mass ratio of the cement, aggregate, fly ash and silica fume is (0.6-0.9):(1-3):(0.1-0.3):(0.01-0.1).

[0040] Preferably, the mass ratio of cement, aggregate, fly ash and silica fume is 0.75:2:0.20:0.05.

[0041] Thixotropy: It is one of the important contents of the rheology of dispersed systems. It refers to a rheological phenomenon in which the viscosity or shear force of the system changes with time under stirring or other mechanical effects.

[0042] The cement is PO42.5 ordinary Portland cement: a hydraulic cementitious material made by grinding Portland cement clinker, 5%-20% of mixed materials and an appropriate amount of gypsum.

[0043] Aggregate is also called "aggregate". It is a granular material that plays a role of skeleton and filling in concrete and mortar. There are two types of aggregate: fine aggregate and coarse aggregate. Generally, natural sand is used, such as river sand, sea sand and valley sand. When natural sand is lacking, artificial sand ground from hard rocks can also be used.

[0044] The aggregate includes sand and gravel, and the particle diameter of the aggregate is between 0.16 and 5 mm.

[0045] Preferably, the mass ratio of the sand to the gravel is (2-4):1, and more preferably, the mass ratio of the sand to the gravel is 3:1.

[0046] Fly ash: It is the fine ash collected from the flue gas after coal combustion. Fly ash is the main solid waste discharged from coal-fired power plants. The main oxide components of fly ash from thermal power plants in my country are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. Waste fly ash can be used as a resource, such as as an admixture for concrete. Fly ash can be purified to obtain microbeads, which are global-shaped, continuous particle size distribution, ultrafine, solid, ultrafine fly ash aluminosilicate fine microbeads (sinking beads).

[0047] Silica fume: also called microsilica powder, scientific name silica fume, is the smoke and dust that escapes with the exhaust gas during the high-temperature smelting of industrial silicon and ferrosilicon in industrial electric furnaces, which is collected and processed by special capture devices. In the escaped smoke, the SiO2 content accounts for about 90% of the total smoke and dust, and the particle size is very small, and the average particle size is almost nanometer level, so it is called silica fume.

[0048] The raw materials also include water, and the ratio of the added amount of water to cement is (0.3-0.5): (0.6-0.9).

[0049] Preferably, the ratio of the added amount of water to cement is (0.35-0.4):0.75.

[0050] The raw materials also include fibers, preferably PP (polypropylene) fibers.

[0051] The added mass ratio of the fiber to water is 0.01:(0.35-0.4).

[0052] The raw materials also include an admixture, and the ratio of the addition amount of the admixture to cement is (0.005-0.01): (0.6-0.9).

[0053] Preferably, the admixture is a main component for maintaining the plasticity of the material and improving the thixotropy, and the admixture includes naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate, and sodium gluconate.

[0054] More preferably, the mass ratio of the naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate and sodium gluconate is 0.8-0.9: 0.002-0.006: 0.001-0.004: 0.03-0.06.

[0055] More preferably, the mass ratio of the naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate and sodium gluconate is 0.85:0.004:0.002:0.05.

[0056] The viscosity of the high thixotropic cement-based material for wet pressing obtained by mixing the above raw materials according to the addition amount specified in the present invention is 1.2-2.4 V / N·ms, and the plastic viscosity is 1.1-3 Pa·s. After adding water and stirring, it has no fluidity and is in a plastic state. At the same time, it has excellent thixotropic properties. Under the action of external force, it can quickly fill the mold and form any desired shape, and can form a block prefabricated component.

[0057] The second aspect of the present invention is to provide a molding method for the high thixotropic cement-based material for wet pressing according to the first aspect of the present invention, the molding method comprising the following steps:

[0058] Step 1, stirring and mixing the weighed raw materials to obtain a mixture;

[0059] Step 2: subject the mixed material to high pressure compaction and molding.

[0060] The above steps are described in detail below.

[0061] In step 1, weighing and loading are carried out in cement tanks, which are closed tanks for storing bulk materials. Tank trucks are used to transport, store and load materials. Sand and gravel are stored in sand and gravel silos, and a separate metering batching machine is used, which is accurate and efficient. Powder metering and water / water reducing agent metering use high-precision metering scales with an error of less than 2%.

[0062] A large amount of air is mixed into the concrete mixture during the mixing process, so the mixture should be regarded as a three-phase system, consisting of solid phase, liquid phase and gas phase.

[0063] The mixing is carried out in a vertical planetary mixer. The mixing planet can cover the bottom plate of the mixing tank once every 5 seconds without any dead corners. High quality and high efficiency, uniform mixing without dead corners, ensure high homogeneity of the material. The mixing capacity of a single pot is about 1000kg.

[0064] The stirring is carried out in a planetary vertical shaft mixer for 3 to 10 minutes. Preferably, the stirring is carried out in a planetary vertical shaft mixer for 5 minutes.

[0065] After the mixture is stirred and formed, it is placed in the material distribution machine. The material distribution machine adopts the volume quantitative discharging method. The discharging amount is accurate and reliable, and it can ensure continuous and uniform movement. The fan blades in the material distribution machine rotate continuously to ensure that the material in the measuring cup is always full.

[0066] In step 2, the high-pressure compaction molding is carried out in a wet static press, which can also play a dehydration role during compaction molding. The static hydraulic press consists of an upper positive film and a lower negative mold, the upper positive film is arranged on a hydraulic cylinder, a module shape is designed on the surface of the positive film, the lower mold is arranged on a support table, a support plane is arranged on the upper surface of the lower mold, and the upper pressing plane corresponds to the lower pressing plane.

[0067] The lower female mold is evenly provided with drainage holes to ensure smooth drainage, and an iron plate is welded at the material discharging port of the material placing machine to ensure that the slurry is evenly arranged in long strips, so that the downward pressure of the upper mold can make the pressed material instantly fill the entire space.

[0068] The press machine opens and closes the mold by lifting the upper template. During the pressing process, the cement components are pressed, exhausted, drained (the water in the slurry is squeezed out and the slurry is evenly dispersed), maintained under pressure and matured, mold opened, and the product is pushed out.

[0069] The single block limit load of the high-pressure compaction molding process is ≥300kg. Preferably, the single block uniformly distributed load of the high-pressure compaction molding process is 450kg.

[0070] In the high-pressure compaction molding process, the molding time of a single block is 15 to 30 seconds, and preferably, the molding time of a single block is 20 seconds.

[0071] The molding speed of the high-pressure compaction molding is 15 to 30 s / block, and preferably, the molding speed of the high-pressure compaction molding is 20 s / block.

[0072] The high-pressure compaction molding process adopted by the present invention is different from the traditional casting method. It adopts static pressing molding. The concrete is thixotropic concrete. The mixed material has basically no fluidity and needs to use external mechanical pressure to make it dense. This method can be demoulded immediately after pressing and molding. The uniformly distributed load of a single piece is ≥300kg, which improves the turnover rate and production efficiency of the equipment.

[0073] Before the pressing begins, the mixture is a loose macroscopic homogeneous body that is not dense. It will only undergo plastic deformation under the action of its own gravity and is considered to be isotropic. After the pressing begins, the mixture is in a three-dimensional stress state and is compressed and deformed under the pressure of the die. The large-size aggregate is first stressed and wedged into the smaller particles. The particles move closer to each other and recombine. The air is discharged through the gaps between the particles. The volume of the green body is significantly reduced, the porosity decreases, and the contact area of ​​the particles increases. Due to the capillary pressure, the loose homogeneous body of solid particles is transformed into a continuous homogeneous body with a certain density, and the plastic strength of the green body is improved. Compared with before pressing, the strength is increased by 30-40%.

[0074] Strength standard of pressed cement-based modules (based on 2.8mm thickness): Under the premise of deflection ≤2mm, concentrated load ≥200kg, uniformly distributed load ≥992kg, and ultimate concentrated load ≥600kg.

[0075] The size standards of the cement block formed by compression molding of the present invention are as follows: side length tolerance ≤0.4mm, plate thickness tolerance ≤0.3mm, surface flatness ≤0.6mm, adjacent edge flatness ≤0.3mm, and the module is normalized and standardized.

[0076] The size of the pressed cement block of the present invention is: 600mm in length, 400mm in width and 44mm in thickness.

[0077] Appearance standards: The floor should be assembled finely, with neat and tight joints, firm bonding, and no debonding. The board covering should be soft, stain-resistant, non-slip, and have no obvious visible color difference, bubbles, or defects.

[0078] Schematic diagram of the microstructure of pressed concrete Figure 1 As shown, from Figure 1 It can be seen that the pressed concrete is mainly composed of cement paste, sand, gravel and pores. There is an interface transition zone (a thin shell with a thickness of 10-50μm) in a small range near the aggregate particles. It has the characteristics of high porosity, oriented growth of calcium hydroxide crystals and dense cracks. It is the weak link of concrete. The interface transition zone is the source of cracks and the preferred location for crack development. It is also the main channel for external media to penetrate into the interior of concrete. It is one of the important factors affecting the durability of concrete.

[0079] The microstructure of the pressed concrete module of the present invention has a small aggregate spacing, is more compact, and water is not easy to pass through the interface transition zone. At the same time, free water is squeezed out of the body, which can prevent the later generation of CSH gel and cause the module volume expansion and cracking. The cement hydration product and the aggregate are more tightly combined, which can effectively improve the mechanical strength of the module.

[0080] Example

[0081] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.

[0082] Example 1

[0083] According to the mass ratio of cement, fly ash, silica fume, sand, gravel, admixture and water of 0.22:0.055:0.015:0.3:0.41:0.06:0.24 (casting type mix ratio), each raw material is weighed to obtain concrete mortar, wherein the aggregate includes sand and gravel, and the particle diameter of the aggregate is between 0.16 and 5 mm. The mixture is directly cast in a test mold for molding.

[0084] Example 2

[0085] According to the mass ratio of cement, aggregate, fly ash, silica fume, admixture and water of 0.75:2:0.2:0.05:0.008:0.35-0.4 (pressed type mix ratio), weigh each raw material to obtain concrete mortar. The aggregate includes sand and gravel, the particle diameter of the aggregate is between 0.16 and 5 mm, and the mass ratio of the sand and gravel is 3:1. The admixture is a mixture of naphthalene-based water reducer, polyvinyl alcohol, sodium dodecyl sulfate and sodium gluconate, and the mass ratio of the naphthalene-based water reducer, polyvinyl alcohol, sodium dodecyl sulfate and sodium gluconate is 0.85:0.004:0.002:0.05.

[0086] Weighing and feeding are carried out in cement tanks, and the raw materials obtained by weighing and feeding are stirred. The stirring is carried out in a vertical axis planetary mixer. The stirring is carried out in a planetary vertical axis mixer for 5 minutes. The stirring planet can cover the bottom plate of the mixing tank once every 5 seconds, without any dead corners, which can ensure high homogeneity of the materials. The stirring amount of a single pot is about 1000kg to obtain the mixed material. After the mixed material is stirred and formed, it is placed in the distribution machine. The distribution machine adopts the volume quantitative discharging method, the discharging amount is accurate and reliable, and can ensure continuous and uniform movement.

[0087] The obtained mixture is placed in a wet static press for high-pressure compaction and molding, which can also play a dehydration role during compaction and molding. The static hydraulic press consists of an upper positive membrane and a lower negative mold. The upper positive membrane is arranged on the hydraulic cylinder, and a module shape is designed on the surface of the positive membrane. The lower mold is arranged on a support table, and a support plane is arranged on the upper surface of the lower mold. The upper pressing plane corresponds to the lower pressing plane. The lower negative mold is evenly arranged with drainage holes to ensure smooth drainage. Iron plates are welded at the material discharging port of the material distributing machine to ensure that the slurry is evenly arranged in long strips, so that the upper mold can press down to make the pressed material instantly fill the entire space. The single-piece uniform load of the high-pressure compaction molding process is 450kg, and the molding speed of the high-pressure compaction molding is 20s / piece.

[0088] The size of the pressed cement block of the present invention is: 600mm in length, 400mm in width, and 44mm in thickness. The size standard of the pressed cement block is: side length tolerance ≤0.4mm, plate thickness tolerance ≤0.3mm, surface flatness ≤0.6mm, adjacent side flatness ≤0.3mm, and the module is normalized and standardized.

[0089] Example 3

[0090] The compression molding was carried out in a manner similar to that of Example 2, except that: fiber was added at a volume fraction of 1%, and the mass ratio of cement, aggregate, fly ash, silica fume, admixture, PP fiber and water was 0.75:2:0.2:0.05:0.008:0.01:0.35-0.4 (compression type mix ratio), and each raw material was weighed to obtain concrete mortar.

[0091] Comparative Example

[0092] Comparative Example 1-1

[0093] The pressing and molding was carried out in a similar manner to Example 2, except that the ratio of fly ash and silica fume added was 0.15:0.1.

[0094] Comparative Example 1-2

[0095] The pressing and molding was carried out in a similar manner to Example 2, except that the ratio of fly ash and silica fume added was 0.125:0.125.

[0096] Comparative Examples 1-3

[0097] The pressing and molding was carried out in a similar manner to Example 2, except that the ratio of fly ash and silica fume added was 0.1:0.15.

[0098] Comparative Example 2-1

[0099] The pressing molding is carried out in a similar manner to Example 2, except that an admixture and a rheological agent are added to improve the fluidity and cohesion of the mixture, and the raw materials are weighed according to the mass ratio of cement, aggregate, fly ash, silica fume, water reducer, rheological agent and water of 0.7:2:0.15:0.15:0.0008:0.0004:0.35-0.4.

[0100] Comparative Example 2-2

[0101] The thixotropic cement-based material was formed in a manner similar to Example 2, except that the ordinary river sand in the raw material was changed to 80-120 mesh washed fine sand, and the raw materials were weighed according to the mass ratio of cement, aggregate, fly ash, silica fume, water reducer, rheological agent and water of 0.7:2:0.15:0.15:0.0008:0.0004:0.35-0.4.

[0102] Experimental example

[0103] Experimental Example 1 Rheological Properties Test

[0104] The rheological properties of the concrete mortars of Examples 1, 2, 3, Comparative Example 1 and Comparative Example 2 were tested respectively.

[0105] Experimental equipment: Mortar mixer: HJW60 forced single-horizontal-shaft concrete test mixer from Wuxi Jianyi Company was used.

[0106] Rheometer: The MCMR rheometer produced by Tianjin Port Source Instrument Co., Ltd. was used to test the rheological properties of concrete mortar. Its principle is to use a concentric cylinder structure, including an outer cylinder as a container and a four-blade structure rotating inner cylinder, such as Figure 2 As shown in Figure 1. The concrete mortar is sheared in the gap between two cylinders, one cylinder is stationary and the other cylinder is rotating. The rotating blades cause the fresh concrete in the gap between the outer cylinder and the blades to plastically deform. During the plastic deformation of the concrete, the MCMR rheometer simultaneously records the actual rotation speed and the torque required to maintain the target speed.

[0107] Experimental steps:

[0108] (1) Before stirring, wipe the stirring pot and stirring blades with a wet cotton cloth, and pour the weighed materials into the stirring pot. First, dry-mix the sand and cement evenly, then add water and mix. Stir for 120 seconds, then stop for 15 seconds, and continue stirring for 60 seconds.

[0109] (2) Pour the stirred mortar into the test kettle of the MCMR rheometer. The test uses an MCMR rheometer with a test barrel radius of 140 mm, a blade height of 125 mm, and a diameter of 125 mm. The blade is rotated by an electric motor, the speed is set to 0.25 rps, and the torque is measured and recorded in real time to draw a stress growth curve. The maximum torque obtained during the test corresponds to the static yield stress of the mortar.

[0110] (3) Then pour out the mortar, re-stir it and put it into the test kettle. Set the speed to increase to 0.5rps within 20s and keep it for 20s as the pre-shear stage. Then the speed is gradually reduced and kept for 5s at each level (test procedure is as follows Figure 3). The rheometer measures torque and speed in real time, and draws the rheological curve through the speed on the x-axis and the equilibrium torque value corresponding to each speed on the y-axis. The Y value is used as the intercept on the torque axis, and the V value is used as the slope of the curve. The curve characteristics (approximately a straight line) show that it conforms to the Bingham characteristics. The MCMR software converts the Y value and the V value into shear stress τ and shear rate γ to draw the rheological curve. The two Bingham parameters, namely the dynamic yield stress τ0 and the plastic viscosity μ0, are determined based on the relationship between the shear stress and the shear rate in the rheological curve. The stress growth curves of Comparative Examples 1-2 and Examples 1-3 obtained by testing are shown in Figure 2. Figure 4 The rheological characteristics of different groups of mortars obtained from the test are shown in Table 1.

[0111] Table 1 Rheological characteristics of different groups of mortar

[0112]

[0113] According to the experimental step (3), the torque (T) and the speed (N) of each group under the stable flow state are tested, and the linear relationship between the torque and the speed is obtained by fitting according to the measured data. The fitting curve of Example 1 is as follows: Figure 5 As shown, the fitting curve of Example 2 is as follows Figure 6 As shown, the fitting curve of Example 3 is as follows Figure 7 As shown, the fitting curve of comparative example 1-1 is as follows Figure 8 As shown, the fitting curve of comparative example 1-2 is as follows Fig. 9 As shown, the fitting curves of Comparative Examples 1-3 are as follows Fig.10 As shown, the fitting curve of comparative example 2-1 is as follows Fig.11 As shown, the fitting curve of comparative example 2-2 is as follows Fig.12 As shown, the intercept G and slope H are obtained, as shown in formula (1). The rheological properties of fresh cement mortar can be described by the Bingham model, as shown in formula (2). According to the Reiner-Riwlin equation, as shown in formula (3), the dynamic yield stress and plastic viscosity of the slurry can be calculated by the G and H values, respectively.

[0114] T = G + HN formula (1);

[0115] τ=τ0+μγFormula (2);

[0116]

[0117] Where:

[0118] T——torque, N / m;

[0119] N——speed, rps;

[0120] τ0——dynamic yield stress, Pa;

[0121] μ——plastic viscosity, Pa·s;

[0122] h——blade height, m;

[0123] R1——blade radius, m;

[0124] R2——radius of test barrel, m.

[0125] according to Figure 4 As can be seen from Table 1, the static yield stresses of Example 2 and Example 3 are 23.451Pa and 30.634Pa, respectively, which are higher than the static yield stress of Example 1 of 19.584Pa, indicating that the fluidity of the pressed cement is significantly better than that of the cast type, and the plastic viscosity of Example 2 is reduced, indicating that the pressed cement mortar is conducive to better shaping.

[0126] Compared with Examples 2-3 and Comparative Example 1, the static yield stress and viscosity of Comparative Example 2 are both reduced, which indicates that the reduction of fly ash content or the addition of rheological agent will reduce the static yield stress of the mortar.

[0127] It can be seen from Table 1 that as the amount of fly ash added decreases (Comparative Examples 2-3, Comparative Example 2 and Comparative Example 1), the dynamic yield stress of the mortar decreases.

[0128] In summary, the mortar obtained by using the raw materials in the high thixotropic cement-based material for wet pressing described in the present invention and mixing them according to the ratio range of the raw materials described in the present invention has a lower plastic viscosity, good fluidity, and higher static yield stress and dynamic yield stress.

[0129] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A high thixotropic cement-based material for wet pressing, characterized in that: The high thixotropic cement-based material for wet pressing is made from raw materials including cement, aggregate, fly ash and silica fume; The mass ratio of the cement, aggregate, fly ash, silica fume and admixture is (0.6-0.9):(1-3):(0.1-0.3):(0.01-0.1).

2. The high thixotropic cement-based material for wet pressing according to claim 1, characterized in that: The mass ratio of the cement, aggregate, fly ash, silica fume and admixture is 0.75:2:0.20:0.

05.

3. The high thixotropic cement-based material for wet pressing according to claim 1, characterized in that: The aggregate includes sand and gravel, and the particle diameter of the aggregate is between 0.16 and 5 mm.

4. The high thixotropic cement-based material for wet pressing according to claim 3, characterized in that: The mass ratio of the sand to the gravel is (2-4):

1.

5. The high thixotropic cement-based material for wet pressing according to claim 4, characterized in that: The mass ratio of the sand to the gravel is 3:

1.

6. The high thixotropic cement-based material for wet pressing according to claim 1, characterized in that: The raw materials also include water, and the ratio of the added amount of water to cement is (0.3-0.5): (0.6-0.9).

7. The high thixotropic cement-based material for wet pressing according to claim 1, characterized in that: The raw materials also include an admixture, and the ratio of the addition amount of the admixture to cement is (0.005-0.01): (0.6-0.9).

8. The high thixotropic cement-based material for wet pressing according to claim 7, characterized in that: The additives include naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate and sodium gluconate.

9. The high thixotropic cement-based material for wet pressing according to claim 8, characterized in that: The mass ratio of the naphthalene-based water reducer, polyvinyl alcohol, sodium lauryl sulfate and sodium gluconate is 0.8-0.9: 0.002-0.006: 0.001-0.004: 0.03-0.06.